Geological and metallogenic evolution of the Palaeoproterozoic Adam Ahmed mouloude region of the Reguibat Shield, Western Sahara - Combs, J (2018)
The Adam Ahmed Mouloude Region of the Liberated Territories of Western Sahara is a previously unstudied region of the Reguibat Shield. Crucially, the region covers a large portion of the ‘Contact Zone’ between the Archaean and Palaeoproterozoic components of the Reguibat Shield, exposed as only a small wedge in neighbouring Mauritania. Two distinct tectonic terranes were identified in the study area, the Leaareig Terrane (ca. 2.22 to 2.15 Ga) in the west and the Sfariat-Bu Daira Terrane (ca. 2.14 to 2.09 Ga) in the east. The Sfariat-Bu Daira Terrane contains the only known anorthosite complex to contain both megacrystic and massif-type anorthosite, normally formed in different tectonic settings at different periods in the Earth’s history. Strong geological and geophysical correlations between the Leaareig and Sfariat-Bu Daira Terrane formed the basis for the proposal of the first geodynamic model for the formation of the West African Craton. This model includes the formation of two volcanic arc terranes (>2.13 Ga), their collision with each other (~2.13-2.12 Ga), a collisional event between the now fully assembled Palaeoproterozoic Terrane with the Archaean Terrane (~2.10-2.09 Ga) followed by mantle delamination and widespread post-collisional magmatism (2.09-2.02 Ga). The Leaareig and Sfariat-Bu Daira Terranes are highly prospective for gold with the potential for other types of mineral deposits including magmatic Ni-Cu-(Co-PGE) sulphide, platinum group element-bearing chromitite, orthomagmatic Fe-Ti-V oxide and Superior-type Iron.